KAJIAN VARIASI TOTAL ELECTRON CONTENT (TEC) DI IONOSFER SEBELUM GEMPABUMI BANTEN 2019 - Ali Azimi (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Earthquakes are one of natural disasters frequently occur in Indonesia. A large earthquake has potential to make detrimental impacts such as casualty and material loss. Researchers around the world have been carrying out studies related to earthquake precursors before an earthquake occurs. The studies of the emergence of total electron content (TEC) anomaly in the ionosphere is one of variable observed by researchers to find the earthquake precursors. Stress accumulation in the lithosphere can cause microfractures resulting in the charged particles may release from those microfractures around the earthquake preparation zone toward the atmosphere and disturb the TEC in the ionosphere. This research aims to find the anomaly of TEC before The 2019 Sunda strait earthquake with M 6.9 close to the province of Banten of Indonesia. This study implements the correlation technique with a threshold. The TEC data obtained from Global Ionospheric Maps (GIM) of the Center for Orbit Determination in Europe (CODE). It shows that an anomaly of TEC was recorded 22 days before the earthquake. The Dst (Disturbance storm time) index is also used to validate that the recorded anomaly is not caused by the geomagnetic storm.